2008
DOI: 10.1055/s-2008-1027609
|View full text |Cite
|
Sign up to set email alerts
|

Langzeitergebnisse nach Iridozyklektomie bei Iristumoren

Abstract: The long-term functional results after Iridocyclectomy are good, whereas complications and recurrences are rare. The 10-year-survival is high. Over a long period iridocyclectomy is a recommendable surgical procedure for removal of progredient tumours of the anterior uvea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…At our evaluation, best-corrected visual acuity of the involved eye at presentation with the suspicious conjunctival lesion was 20/20 in 2 cases, 20/30 in another and light perception (LP) in a fourth case, and median intraocular pressure (IOP) was 14mmHg (mean: 13, range: [12][13][14]. Examination of the suspicious conjunctival lesions revealed a single small (<5mm in diameter) red lesion in one case, large single multilobed pink lesion in another, and several small pigmented lesions in 2 cases.…”
Section: Clinical Findings and Managementmentioning
confidence: 78%
See 2 more Smart Citations
“…At our evaluation, best-corrected visual acuity of the involved eye at presentation with the suspicious conjunctival lesion was 20/20 in 2 cases, 20/30 in another and light perception (LP) in a fourth case, and median intraocular pressure (IOP) was 14mmHg (mean: 13, range: [12][13][14]. Examination of the suspicious conjunctival lesions revealed a single small (<5mm in diameter) red lesion in one case, large single multilobed pink lesion in another, and several small pigmented lesions in 2 cases.…”
Section: Clinical Findings and Managementmentioning
confidence: 78%
“…4 In their series they described 3 cases that developed extraocular relapse, but which also had a concurrent intraocular component. Daubner et al monitored 20 iris melanoma cases for a mean time of 16.4 years after performing iridocyclectomy and found that 2 relapsed, but only intraocularly, 14 and no case of extraocular relapse was reported in a review by Müller on 70 resected iris malignant tumours (presumably most were uveal melanoma). 24 Shields et al reported on 169 iris melanoma patients, 102 of which were treated by local resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ein lokales Tumorrezidiv wurde in bis zu 10 % der Fälle beschrieben. Das Sehvermögen kann in 57 % der Fälle nach 10 Jahren > 0,5 erreichen [72].…”
Section: Ergebnisse Und Komplikationenunclassified
“…Nur etwa 2-3% der uvealen Melanome entstehen in der Iris, die verbleibenden 97-98 % bilden Ziliarkörper-und Aderhautmelanome [3]. Obwohl Melanome der Uvea sehr langsam wachsen, können sie doch metastasieren und somit zum Tod des Patienten führen [4]. Die Angaben in der Literatur zur Häufigkeit von Fernmetastasen bei Tumoren der vorderen Uvea schwanken zwischen 3 und 5 % [3,5].…”
unclassified